Comparison of the hemodynamic responses of phase I cardiac rehabilitation to the DiGXT in the post-surgical population - Moes, Darlene M. (My University, 1982)
This ex post facto study compared the hemodynamic responses of 4 progressive activity levels of phase I cardiac rehabilitation and the DiGXT at similar MET levels. Ninety-three Ss, 13 females and 80 males, were selected from the medical files at La Crosse Lutheran Hospital, La Crosse, Wisconsin after undergoing CABG and/or valve replacement. Ss completed activity levels 1, 2, and 3, as well as Stages 1 and 2 of the DiGXT. Means and standard error of the means were used to describe the data in a descriptive fashion. An ANOVA with repeated measures and a Scheffe test were used to analyze the following variables : HR, SBP, and DBP. A t-test for paired means also was used to analyze HR, SBP, and DBP. Sig diff (pC.01) were found among the resting DBP values. There were no sig diff between the resting and post-exercise HR, SBP, and DBP responses to the 4 activity levels. Sig diff (pC.01) was found among the HR and SBP responses to the 2 activity levels as compared to the 2 stages of the DiGXT. Sig diff (pC.01) was found between the HR response to activity level 4 and the DiGXT stage 3. Thus, sig diff were demonstrated among the HR and SBP responses recorded after completing phase I activities and the responses recorded during the DiGXT at similar MET levels . Therefore, it was concluded that the DiGXT can provide valuable information for writing an appropriate exercise prescription for phase I1 cardiac rehabilitation.
Keywords: Hemodynamics; Exercise therapy; Heart - Diseases - Patients - Rehabilitation